Design and fabrication of microwave oven rack at the west station food outlet - Mohd Hafizul Hakim, Basharudin (2012)
This report presents about the hangingmicrowave oven rack that usually used for place the microwave oven especially at kitchen. This is the device which important in order to place the microwave oven easily, and can save the workplace utilization in kitchen. Besides that, it also has other function like ventilation system where it used to reduce the hot air or smoke surrounding which cause by the microwave oven.. The idea of the fabricate for this hanging rack is based on student’s creativity. The selection of suitable materials in the fabricating of this hanging rack is a loaded material which has ease to form, long life-span, can detain heavy load and corrosion resistance. Materials are used for the fabrication of the hanging rack is a galvanized plate and mild steel.